Comparison of the outcomes of individuals with medically attended influenza A and B virus infections enrolled in 2 international cohort studies over a 6-year period: 2009-2015 - Dwyer, DE; Lynfield, R; Losso, MH; Davey, RT; Cozzi-Lepri, A; Wentworth, D; Uyeki, TM; Gordin, F; Angus, B; Qvist, T; Emery, S; Lundgren, J; et al. (Oxford University Press, 2017)
Outcome data from prospective follow-up studies comparing infections with different influenza virus types/subtypes are limited.Demographic, clinical characteristics and follow-up outcomes for adults with laboratory-confirmed influenza A(H1N1)pdm09, A(H3N2), or B virus infections were compared in 2 prospective cohorts enrolled globally from 2009 through 2015. Logistic regression was used to compare outcomes among influenza virus type/subtypes.Of 3952 outpatients, 1290 (32.6%) had A(H1N1)pdm09 virus infection, 1857 (47.0%) had A(H3N2), and 805 (20.4%) had influenza B. Of 1398 inpatients, 641 (45.8%) had A(H1N1)pdm09, 532 (38.1%) had A(H3N2), and 225 (16.1%) had influenza B. Outpatients with A(H1N1)pdm09 were younger with fewer comorbidities and were more likely to be hospitalized during the 14-day follow-up (3.3%) than influenza B (2.2%) or A(H3N2) (0.7%; P < .0001). Hospitalized patients with A(H1N1)pdm09 (20.3%) were more likely to be enrolled from intensive care units (ICUs) than those with A(H3N2) (11.3%) or B (9.8%; P < .0001). However, 60-day follow-up of discharged inpatients showed no difference in disease progression (P = .32) or all-cause mortality (P = .30) among influenza types/subtypes. These findings were consistent after covariate adjustment, in sensitivity analyses, and for subgroups defined by age, enrollment location, and comorbidities.Outpatients infected with influenza A(H1N1)pdm09 or influenza B were more likely to be hospitalized than those with A(H3N2). Hospitalized patients infected with A(H1N1)pdm09 were younger and more likely to have severe disease at study entry (measured by ICU enrollment), but did not have worse 60-day outcomes.